Analysis of Human Resource Needs for Organizing Events in the MICE Industry: A Study in South Sulawesi Province - Amiruddin Hamzah; Muh Rusdi; Andi Abriani (Politeknik Pariwisata Makassar, 2024)
This research analyzes human resource needs in the MICE (Meetings, Incentives, Conferences, and Exhibitions) industry in South Sulawesi Province. This research focuses on three main aspects: the development of the event business, the need and availability of human resources for event organizers, and the skill competencies needed by the industry in organizing events in South Sulawesi. The research method used is qualitative research. This data is analyzed to provide a comprehensive description of the actual conditions and human resource needs in the MICE industry in South Sulawesi and become a reference for stakeholders in developing human resources in the MICE industry sector. The research results show that 1). The development of the Event Business in South Sulawesi has great potential because it is supported by adequate infrastructure such as the International Airport, toll roads, Convention Center Building, malls, hotels, and transportation facilities) and the availability of complete entertainment and shopping centers, culinary, and support. local community. 2). - There are not enough MICE HR professionals in South Sulawesi. Many events are held each year, but not enough workers have the right skills. Event service entrepreneurs often have to recruit volunteers who are not competent. 3). The skill competencies needed by the industry in organizing events in South Sulawesi are competencies for Event Registration, Event Stand Building, Event Logistics, Event Marketing Communication, Event Venue Management, Event Liaison Officer, Event Destination Bidding certification clusters in the 2020 MICE field certification scheme.